Kajian Biaya Operasi Kereta Api - Jamaludin, Jamaludin; Astuti, Septiana Widi (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2018)
This research discusses the calculation of railroad operating costs, the railroad operating costs are very important because it is related to determining the level of profit from setting a railroad transportation service tariff. The current train operating costs are indicated to be not yet competitive compared to the same mode operating costs in other countries, this study looks at the constituent components of train operating costs based on predetermined regulations. Based on the results of the analysis of the calculation of railroad operating costs at present the percentage of railroad direct costs is 23% and the percentage of railroad indirect costs is 77%. The percentage of costs is still large in the indirect costs which resulted in not yet being able to obtain competitive operating costs, whereas when compared to the costs of railroad operations abroad, in the UK the maintenance costs of trains are around 16% - 30% while in Indonesia around 6%. The cost of railway operations in the UK is 66% -73% while in Indonesia it reaches around 91%. The author suggests to reduce the percentage of indirect costs by making profitable business breakthroughs.